Pengaruh Risiko Kredit, Risiko Pasar, Dan Risiko Likuiditas Terhadapkinerja Perbankan Pada Tahun 2016-2020 (Studi Di Bank Pembangunan Daerah Indonesia) - Marsha Caesarani; Gusganda Suria Manda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The role of the banking system uses more of the financial system. The financial system has a very positive impact on bank performance. This study is to understand the risk of influence on banking which is analyzed using NPL, NIM, LDR ratios related to financial performance at Regional Development Banks in Indonesia. The evidence used is from the annual financial report of the Financial Services Authority. The sample quantity is 5 Regional Development Banks in Indonesia using a time span from 2016-2020. In conducting observations using SPSS version 25 technique where observation data prove simultaneously, NPL, NIM, and LDR have a relevant impact on ROA. In partial, relevant NPL has a negative impact on ROA, NIM is relevant and has a positive impact on ROA, LDR is irrelevant and has a negative impact on ROA. In this observation, it is generated that Banking Risk as measured by the three ratios contained has a relevant impact on financial performance. Make sure that the Regional Development Bank is obliged to be able to recognize its business actions. In the observation where the company must include, reduce NPL and LDR because it will have a negative impact on ROA. Also increases NIM because it has a positive impact on ROA. Keywords: Financial Performance, NPL, NIM, LDR, ROA.